Comparison of masticatory efficiency in unilateral and free-sided chewing - Kohno, Shoji; Kaneda, Koh; Medina, Raul; Kohno, Tsuguyoshi; Toyooka, Eiichi; Kido, Toshiaki (Nihon Gaku Koukou Kinou Gakkai zasshi, 1997)
During mastication, food is subjected to compressive and crushing forces on the occlusal surfaces in order to form a food bolus; this has led most studies of masticatory efficiency to deal with the mechanical degradation of the food particles only, thus neglecting the matter concerning the flow of the food bolus in the oral cavity. Using a modified sieving method, we have previously reported that the food bolus flows through the occlusal surfaces into the proper cavity of the mouth to proceed to deglutition. This method enabled us to evaluate not only the particle size but the distribution of the food bolus in the oral cavity during mastication. In this study, we applied this method to determine the effect of the unilateral mastication caused by occlusal problems on the masticatory efficiency. Eight fully dentate subjects sitting upright in a dental chair were asked to chew three grams of dried peanuts in two masticatory schemes: 1) Unilateral chewing. The subject was deliberately forced to chew the test food only in one side and not to alternate sides of mastication. 2) Free-sided chewing. The subject was asked to chew as usual. In both masticatory schemes, two analyses were done: a) the number of masticatooy strokes required for swallowing was counted by asking the subject to chew the experimental food bolus until swallowing, and b) to determine the distribution of food particles in the vestibule of the mouth and proper oral cavity, the subject made 20 masticatory strokes on the test food, then collected the food particles accumulated in these zones and weighed them after drying them. Results: 1) A significantly higher number of chewing strokes were required to swallow in the unilateral chewing scheme than in the free-sided chewing one. 2) After completing 20 chewing strokes the proportion of food particles in the proper oral cavity was heavier in free-sided chewing than in the unilateral. Conclusion: The food particles flow faster to the proper cavity of the mouth and become readily available for deglutition in free-sided chewing than in an unilateral chewing scheme. From this we infer that unilateral mastication must be inferior in masticatory efficiency.